Effects of amending urea with humic acid and acid sulphate soil in reducing ammonia loss and nitrogen uptake by maize plant - Mohd Yusuff, Mohd Taufik (2011)
The need to reduce ammonia (NH3) loss from nitrogen based fertilizers such as urea has been recognized. Amending urea with humic acid (HA) and acid sulphate soil could control urea hydrolysis and reduce NH3 volatilization. This approach may contribute to urea-N use efficiency. The objectives of this study were to: 1) evaluate the effect of mixing urea with HA and acid sulphuric soil on NH3 loss, and 2) investigate the effect of the selected urea- ASS-HA mixture on N uptake by maize plant. In this study, peat soil was used because it contains about 40% HA, while ASS is abundant in Malaysia. Both acid sulphate soil and HA used were oven dried and ground to pass a 250 μm sieve before being thoroughly mixed with urea based on treatment ratios. The mixtures were mixed thoroughly on a reciprocal mechanical shaker at 200 rpm. All the 14 treatments including 2 controls, mainly soil without fertilizers (T1) and urea without additives (T2) were evaluated in a laboratory study to determine their effect on NH3 loss, soil exchangeable ammonium (NH4 +) and soil available nitrate (NO3 -) using a closed dynamic air flow system. Out of the 12 mixtures studied, 3 treatments, 2.02 g urea + 0.75 g HA + 0.75 g ASS (T5), 2.02 g urea + 0.75 g HA (T9) and 2.02 g urea + 1.00 g HA (T10) significantly reduced NH3 volatilization compared with T2 (urea alone). The treatments selected based on their performance in controlling NH3 loss (T5, T9 and T10) were further investigated in a pot experiment (greenhouse) together with T1 and T2 (controls). Again the mixtures improved soil pH and retention of soil exchangeable ammonium. However, in terms of dry matter production and nutrient uptake (N, P, and K) on Zea mays L. (test crop; variety Masmadu) the effect was statistically similar to that of urea alone. Three to five cropping cycles may be required to confirm this finding on Nyalau Series and also reducing the effect of ammonia volatilization with efficient application of urea based fertilizers.